Assessment of HIV‐related stigma in a US faith‐based HIV education and testing intervention. Issue 3 (13th November 2013) - Berkley‐Patton, Jannette Y; Moore, Erin; Berman, Marcie; Simon, Stephen D; Thompson, Carole Bowe; Schleicher, Thomas; Hawes, Starlyn M
Abstract : Introduction: The African American church is a highly influential institution with the potential to greatly increase the reach of HIV prevention interventions and address HIV‐related stigma in US African American communities. However, there are few studies on HIV‐related stigma and African American church populations. This study explored HIV‐related stigma among church and community members participating in an HIV education and testing intervention pilot study in African American churches, named Taking It to the Pews. Methods: Four African American churches located in Kansas City, MO and KS, were randomized to either intervention or comparison groups. Churches assigned to the intervention group received religiously tailored HIV education, testing and compassion messages/activities (e.g., sermons, brochures/church bulletins, testimonials) via the Taking It to the Pews HIV Tool Kit. Comparison churches received non‐religiously tailored HIV information. HIV‐related stigma was assessed with 543 church members and with community members served through church outreach services (e.g., food/clothing pantries, social services) in the four churches. Participants completed surveys at baseline, 6 months and 12 months to assess their HIV‐related stigma beliefs, exposure to intervention components and satisfaction with the study. Results: At baseline, HIV‐related stigma beliefs were similar across experimental groups and were quite low. Mean HIV‐related stigma scores were not significantly different between experimental groups at 6 months ( p =0.92) or at 12 months ( p =0.70). However, mean HIV‐related stigma scores within both groups showed decreasing trends at six months, which approached significance. Analysis of previously studied HIV‐related stigma factors (e.g., age, gender, income, HIV knowledge, religiosity) did not yield changes in the null findings. Intervention group participants were highly exposed to several intervention components (sermons, HIV resource tables, posters, brochures/church bulletins). Overall, participants were highly satisfied with the intervention pilot study. Conclusions: African American churches may be well positioned to increase the reach of HIV prevention interventions to church and community members and could serve an important role in addressing HIV‐related stigma in their church communities. Future research is needed on measuring HIV‐related stigma beliefs and on testing intensive, scalable, religiously tailored HIV interventions to impact HIV‐related stigma in African American churches.